Perbandingan Efektivitas Injeksi Agen-Agen Anti-Vegf pada Pengobatan Age-Related Macular Degeneration - Nahak, Petronela Bhoko; Arsita, Elli; Wastitiamurti, Ritsia Anindita (Jurnal MedScientiae, 2024)
Age-related macular degeneration (AMD) is one of the leading causes of blindness in people >60 years of age in developed countries. The pathogenesis of neovascular AMD involves increased choroidal vascular permeability, leading to hypoxia and the production of pro-inflammatory and pro-angiogenic factors, particularly vascular endothelial growth factor (VEGF). Treatment of neovascular AMD involves anti-VEGF therapy, which inhibits abnormal blood vessel growth. Numerous studies have demonstrated the effectivity and side effects of each Anti-VEGF agent. Based on this background, the author is interested in conducting a literature review that summarizes the effectivity and side effects of each Anti-VEGF agent. The method used was Literature Review. Journals were collected using GoogleScholar or Google Scholar, PubMed and Proquest within the last 10 years. A total of 10 journals that met the inclusion-exclusion criteria were reviewed and tested for eligibility with the Ottawa score. The results of this literature review showed that anti-VEGF agents including bevacizumab, ranibizumab, aflibercept, pegaptanib sodium, brolucizumab and abicipar pegol have been shown to be equally effective in improving vision and maintaining stable vision in neovascular AMD patients. However, these anti-VEGF treatments can also cause side effects such as intraocular inflammation, increased intraocular pressure and vascular problems.